2021
DOI: 10.1364/ol.425186
|View full text |Cite
|
Sign up to set email alerts
|

Generation of optical vortex lattices by a coherent beam combining system

Abstract: Owing to the unique features in intensity and phase structures, optical vortex lattices (OVLs) have attracted intensive attention and promoted various applications. However, the power scaling of OVLs always presents a critical challenge. Here we take advantage of the brightness enhancement of coherent beam combining (CBC) technology and propose an architecture for creating OVLs based on the CBC system. In the experiment, by utilizing the stochastic parallel gradient descent algorithm, the dynamic phase noises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
13
0
3
Order By: Relevance
“…In the conventional CBC system for generating the OVB, the phases differences of the laser beam array can be compensated to be 0 or an integer multiple of 2π during the phase locking. The desired phases structures can be generated by the conjugated phase shifts of the LCs [41] or SLM [32]. The phase locking system is complicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the conventional CBC system for generating the OVB, the phases differences of the laser beam array can be compensated to be 0 or an integer multiple of 2π during the phase locking. The desired phases structures can be generated by the conjugated phase shifts of the LCs [41] or SLM [32]. The phase locking system is complicated.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas, as a promising study, few has been reported about generating and manipulating the OVBA with the piston phase array via the CBC technique. In our previous work, we preliminarily proposed and experimentally demonstrated an architecture for creating the OVBA based on the CBC system [41]. The hexagonal close-packed OVBA consists of spatially distributed OAM beams could be generated effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Прогрессия может быть возрастающей по модулю каждого члена, убывающей или стационарной. Первый член прогрессии имеет вид a k exp[-(r / w) 2 + ikm], последний член прогрессии a n exp[-(r / w) 2 + inm], знаменатель прогрессии a exp(im. Параметры семейства оптических вихрей: целые числа (k, n, m) и действительное число a. Если a < 1, то прогрессия убывающая и ТЗ суперпозиции равен топологическому заряду первого члена прогрессии (TC = km, k < n), так как первый член описывает оптический вихрь с наибольшей мощностью в суперпозиции.…”
Section: заключениеunclassified
“…Например, в [1] экспериментально исследовались цилиндрические векторные пространственновременные оптические вихри. В [2] предложена оптическая схема для генерации 2D-решетки оптических вихрей. В [3] экспериментально создана 3D-решетка оптических вихрей.…”
Section: Introductionunclassified
“…The fast OAM mode switching can be realized with the electric phase modulators [37] , and the response frequency is over several gigahertz. The technique of generating the OAM beam with an OPA via the CBC technique has been significantly investigated [36,37,[42][43][44][45] . Both a single OAM beam and the OAM beam array could be generated effectively with the OPA [46] .…”
Section: Introductionmentioning
confidence: 99%